1993
DOI: 10.1128/jcm.31.3.598-605.1993
|View full text |Cite
|
Sign up to set email alerts
|

High-level expression of a 56-kilodalton protein gene (bor56) of Rickettsia tsutsugamushi Boryong and its application to enzyme-linked immunosorbent assays

Abstract: The 56-kDa protein of Rickettsia tsutsugamushi, which is located on the rickettsial surface, has been shown to be an immunodominant antigen. The gene that encodes the 56-kDa protein of R. tsutsugamushi Boryong (bor56) was cloned. Sequencing revealed an open reading frame of 1,602 bp encoding 534 amino acids with a molecular weight of 56,803. The 56-kDa protein ofR. tsutsugamushi Boryong (Bor56) was expressed as a fusion protein with the maltose-binding protein of Escherichia coli by deleting 252 bp from the 5'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 23 publications
1
59
0
Order By: Relevance
“…However, the strains could be divided into two subtypes, KR-1 and KR-2, by RFLP. The Boryong strain was isolated in Korea (2) and the 56-I(Da protein gene was cloned and sequenced by Kim et al (11). They reported that the 56-kDa protein of this strain showed 99.1% homology at the amino acid sequence level (5 amino acid replacements in 532 residues) with that of Kuroki strain (prototype), and the theoretical RFLP patterns of the Boryong strain generated by computer analysis with a program for restriction mapping were identical with those of Kuroki strain in all 5 endonuclease digestions, indicating that Boryong strain should be included in the KR-1 subtype.…”
Section: Discussionmentioning
confidence: 99%
“…However, the strains could be divided into two subtypes, KR-1 and KR-2, by RFLP. The Boryong strain was isolated in Korea (2) and the 56-I(Da protein gene was cloned and sequenced by Kim et al (11). They reported that the 56-kDa protein of this strain showed 99.1% homology at the amino acid sequence level (5 amino acid replacements in 532 residues) with that of Kuroki strain (prototype), and the theoretical RFLP patterns of the Boryong strain generated by computer analysis with a program for restriction mapping were identical with those of Kuroki strain in all 5 endonuclease digestions, indicating that Boryong strain should be included in the KR-1 subtype.…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of 56-kDa genes of six strains, Gilliam, Karp, Kato, Kawasaki, Kuroki and Shimokoshi, were reported previously [9^11]. Sequences of the genes of Yonchon and Boryong strains isolated in South Korea have been reported in Korean studies [12,13], and the sequences of TA678, 686, 716 and 763 strains obtained in Thailand [4] and the Sxh 951 strain in China were cited from the GenBank. The sequencing of other strains in Table 1 was carried out in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 shows the DNA sequences of the 0.6-kb PCR products from the 4 strains in Miyazaki, and from the Karp strain reported by Stover et al (10). The DNA sequences of the PCR products from the Tazume and Hirano strains showed a high degree of homology (98.8%), and these two strains were also highly homologous (99.0%) to the reported sequence of the Boryong strain (6). The DNA sequence of the Yoshimura strain revealed a high degree of homology (96.2%) to the Karp strain (10).…”
mentioning
confidence: 72%
“…The antigenic variation of O. tsutsugamushi is dependent on a strain-specific 56-kDa protein (12 encoding this 56-kDa protein antigen have been cloned and sequenced from the Karp (10), Gilliam, Kato, Kawasaki, Kuroki, Shimokoshi (8,9) and Boryong strains (6). To clarify the association of each strain in Miyazaki Prefecture with the representative strains, we sequenced the PCR products from Irie, Hirano, Tazume and Yoshimura strains.…”
mentioning
confidence: 99%